Heart disease prevention project: a randomised controlled trial in industry. Issue 6216 (15th March 1980) - Rose, G; Heller, R F; Pedoe, H T; Christie, D G
Abstract : Twenty-four factories or other occupational groups, employing 18 210 men aged 40 to 59, were formed into matched pairs. One of each pair was allocated randomly to receive a five to six year programme of medical examinations and intervention to reduce the levels of the main coronary risk factors. Men at factories in the intervention group were given advice on dietary reduction of plasma cholesterol concentrations, stopping or reducing cigarette smoking, regular exercies for the sedentary and reduced energy intake for the overweight, and hypertension was treated. The programme was delivered mainly through existing occupational medical services, helped by a small central staff. Personal consultations were largely confined to men with a high risk of developing coronary heart disease. Changes in risk factors were assessed by regular standardised examinations of random samples of men. The spread of information by general propaganda proved easy, but a change in habits seemed to require personal contact. Small but significant reductions occurred, mainly in the high-risk group, but these were not sustained when pressure was relaxed.